Development Indices of Gongronema latifolium Benth Domesticated in Otuoke Terrestrial Habitat, Bayelsa State, Nigeria - Mbosowo M., Etukudo; Samuel E., Osim (European Scientific Journal, ESJ, 2018)
The effects of physico-chemical properties of two soil sampling locations on the proximate and mineral nutrients contents of Gongronema latifolium Benth were examined in Otuoke secondary forest habitat, in Bayelsa State, Nigeria. Leaf samples of Gongronema latifolium and soil (0-20 cm depth) samples were randomly collected from two sites in the study area. Three replicates were maintained for each treatment using randomized complete block design. The pH of 5.10 was recorded at location 1 while that of location 2 was 5.00. The contents of calcium, magnesium, sodium, phosphorus, iron, copper and zinc were higher in leaves of G. latifolium at location 1 than those of location 2, while the content of potassium was higher in leaves of G. latifolium at location 2 than those of location 1. The moisture, protein, lipid and fibre contents in leaves of G. latifolium were higher at location 1 than those of location 2, while the contents of ash and carbohydrate in leaves of G. latifolium were higher at location 2 than those of location 1. This study showed that the nutritional status of G. latifolium was affected by the sampling locations of the study area, hence, appropriate cultural practices are needed in the area in order to create favourable soil conditions for optimum growth and development of the test plant.